Cyber Sextortion: An Exploratory Analysis of Different Perpetrators Engaging in a Similar Crime - O’Malley, Roberta Liggett (Journal of interpersonal violence, 2022)
Sextortion, a portmanteau of “sexual” and “extortion,” is the threat to distribute intimate, sexual materials unless a victim complies with certain demands. Cyber sextortion is part of a larger continuum of image-based sexual offending in which images are used for harm. Despite the serious nature of this crime, there exists a dearth of empirical knowledge of sextortion. This article employed a qualitative content analysis of media articles and court documents to explore the crimes of 152 cyber sextortion offenders. Characteristics of offenders, victims, demands, and methodology were identified and synthesized to generate a qualitative understanding of offenders who employed cyber sextortion. The results revealed four different themes of offenders based on crime characteristics: minor-focused cyber sextortion offenders, cybercrime cyber sextortion offenders, intimately violent cyber sextortion offenders, and transnational criminal cyber sextortion offenders. The diverse nature of cyber sextortion has implications for crime control policies. Certain offenders are more likely to be apprehended and prosecuted depending on the crime victim and methodology. In addition, there has been a lack of legislative action targeting cyber sextortion, which limits legal recourse available for victims. We discuss the contribution of this work to the broader literature on cyber sextortion and address some of the challenges that this crime presents to the criminal justice system.